1988
DOI: 10.1002/mus.880111211
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic study of denervated and reinnervated neuromuscular junction

Abstract: Morphological changes of the subneural apparatus (SNA) during denervation and reinnervation are demonstrated using the hamster peroneus longus muscle. One week after nerve section, synaptic grooves (SGs) were more shallow, with lowered sarcoplasmic ridges. After 4 weeks, the whole SNA area was elevated above the sarcolemma as a flat plate, which persisted as a fusiform bulge for more than 8 weeks. There was a rapid and progressive decrease in the number of junctional folds (JFs) and slit-to-pit transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The intense staining for caveolin-3 at the NMJ demonstrated in the present study points to a significant concentration of this molecule at the NMJ, but at the light microscopic level the basis for this cannot be determined. Although high-power electron micrographs do not suggest an unusually high concentration of caveolae in relation to surface membrane area, the great structural complexity of the postsynaptic folds in normal rat muscle (Matsuda et al 1988;Ogata 1988;Oki et al 1990) could increase the total membrane surface in the area of the NMJ to the point where it would be reflected as an intense concentration at the light microscopic level. In the absence of immunoelectron microscopy it is not possible to determine if caveolin-3 is associated with other subcellular structures in the NMJ.…”
Section: Discussionmentioning
confidence: 92%
“…The intense staining for caveolin-3 at the NMJ demonstrated in the present study points to a significant concentration of this molecule at the NMJ, but at the light microscopic level the basis for this cannot be determined. Although high-power electron micrographs do not suggest an unusually high concentration of caveolae in relation to surface membrane area, the great structural complexity of the postsynaptic folds in normal rat muscle (Matsuda et al 1988;Ogata 1988;Oki et al 1990) could increase the total membrane surface in the area of the NMJ to the point where it would be reflected as an intense concentration at the light microscopic level. In the absence of immunoelectron microscopy it is not possible to determine if caveolin-3 is associated with other subcellular structures in the NMJ.…”
Section: Discussionmentioning
confidence: 92%
“…After 2-3 weeks of denervation, the fibres became noticeably atrophied when compared with innervated fibres, and fibrillation was often observed. The endplate became difficult to identify without the aid of oc-BuTX, although it could often be discerned as a local bulging of the sarcolemma (see also Matsuda, Oki, Kitaoka, Nagano, Nojima & Desaki, 1988). No obvious change in the pattern or appearance of the a-BuTX fluorescence was apparent, even after 6 weeks of denervation.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it is interesting that nestin becomes localized to the synaptic site during the postnatal period when junctional folds are reported to be first forming (Marques et al, 2000). Arguing against this possibility is the observation that nestin essentially disappears from rat neuromuscular junctions after denervation, whereas the folds persist (Miledi and Slater, 1968), although some observations suggest that these folds begin to change the size of their openings to the synaptic space, their frequency, and the depth of their penetration into the sarcoplasm with longer periods of denervation (Matsuda et al, 1988). Froehner et al (1987) suggested the possibility that the intermediate filament desmin, which is also localized to the junction, might be involved in postsynaptic folding but primarily discounted this possibility because this filament is present at junctions that have no synaptic folds.…”
Section: Discussionmentioning
confidence: 99%